What Factors Contribute to Attrition at Day-time Centres in the Skills Training Programme - Pierre, Florence (My University, 2015)
Employing a narrative approach, this study sought to record and analyse technical and vocational education and training (TVET) trainees’ experiences with non-completion of the courses in which they enrolled. Data were collected through interviews with 10 trainees who had dropped out of programmes at three full-time TVET centres in Trinidad and Tobago. Analysis of the narratives of the lived experiences of the trainees indicated that family and social factors, financial factors, institutional factors, and student trajectories were key contributors to trainee attrition.
Keywords: Technical and vocational education and training; Trainees; Dropouts; Factor analysis; Trinidad and Tobago